Excel 2013 formulas and functions - McFedries, Paul (MrExcel library., 2013)
Master core Excel 2013 tools for building powerful, reliable spreadsheets! Excel expert Paul McFedries shows how to use Excel 2013's core features to solve problems and get the answers you need. Using real-world examples, McFedries helps you get the absolute most out of features and improvements ranging from FlashFill to Excel's newest functions. Along the way, you discover the fastest, best ways to handle essential day-to-day tasks ranging from generating account numbers to projecting the impact of inflation. Becoming an Excel expert has never been easier! You'll find crystal-clear instructions; insider insights; even complete step-by-step projects for building timesheets, projecting cash flow, aging receivables, analyzing defects, and more.. • Quickly create powerful spreadsheets with FlashFill • Use conditional formatting to instantly reveal anomalies, problems, or opportunities • Analyze your data with standard tables and PivotTables • Use complex criteria to filter data in lists • Understand correlations between data • Perform sophisticated what-if analyses • Use regression to track trends and make forecasts • Build loan, investment, and discount formulas • Validate data, troubleshoot problems, and build more accurate, trustworthy spreadsheets About MrExcel Library: Every book in the MrExcel Library pinpoints a specific set of crucial Excel tasks and presents focused skills and examples for performing them rapidly and effectively. Selected by Bill Jelen, Microsoft Excel MVP and mastermind behind the leading Excel solutions website MrExcel.com, these books will • Dramatically increase your productivity—saving you 50 hours a year or more • Present proven, creative strategies for solving real-world problems • Show you how to get great results, no matter how much data you have • Help you avoid critical mistakes that even experienced users make CATEGORY: Spreadsheets COVERS: Microsoft Office Excel 2013.